Una Escuela Llamada América: Documentary film and photography as ethnographic tools for reflexive social research - Mardones Marshall, Antonia (2022)
How can documentary strategies advance sociological insights beyond academia? This photo-essay analyzes the process of producing the documentary film “Una Escuela llamada América'' with immigrant children in Arica – the northernmost city in North Chile, only 20 kilometers south from the frontier with Peru. We reflect upon the documentary’s production and its relationship with social research in order to show how visual narratives can serve public debates. The photographs included in this work document different stages of the process of narrative-making. Ultimately, these visual sources highlight the agency of the film’s protagonists in framing their own stories in the collective assembling of the audiovisual pieces. Film directors and participants are thus crucial agents in the effort of producing this piece of visual sociology.